Optimal distribution network reconfiguration with penetration of distributed energy resources - Syahputra, Ramadoni; Robandi, Imam; Ashari, Mochamad (2014 1st International Conference on Information Technology, Computer and Electrical Engineering (ICITACEE), 2014)
This paper presents an optimal distribution network reconfiguration with penetration of distributed energy resources (DER). The reconfiguration is done to achieve the minimum active power loss of radial distribution networks with DER penetration. As a further matter, the presence of DER to the distribution systems has become some problems such the increase of the voltage at which there are many DER. In this study, the technique of network reconfiguration is based on an extended fuzzy multi-objective. Multi-objective function are considered for the power loss minimization, deviation of bus voltage, and load balancing among the feeders, while subject to a radial network structure in which all loads must be energized. The extended fuzzy multi-objective for reconfiguration of distribution network has been tested on Yogyakarta 60-bus distribution network data. The test results show that a 3.83% of Yogyakarta 60-bus network power loss reduction is achieved by the method. Also, the improvement of the voltage profile at each bus is also achieved with this method.